Modulation of lung CD11b+ dendritic cells by acupuncture alleviates Th2 airway inflammation in allergic asthma - Cheng, Mi; Shang, Pan-Pan; Wei, Dan-Dan; Long, Jie; Zhang, Xue; Wu, Quan-Long; Bassi, Gabriel Shimizu; Wang, Yu; Chen, Yan-Jiao; Yin, Lei-Miao; Yang, Yong-Qing; Xu, Yu-Dong (Chinese medicine, 2025)
Allergic asthma features Th2-mediated airway inflammation, with dendritic cells (DCs) playing a crucial role. Acupuncture shows promise in modulating immune responses, yet its mechanisms in allergic asthma are not well understood. This study explores how acupuncture alleviates Th2 airway inflammation by modulating lung CD11b DCs. Female BALB/c mice were assigned to control and asthma model groups, with subsets receiving acupuncture at Dazhui (GV14), Fengmen (BL12), and Feishu (BL13). We evaluated airway hyperresponsiveness (AHR), immune cell infiltration, histological changes, Th2 cytokine production, and serum IgE levels. The effects of acupuncture serum on T cell activation and bone marrow-derived dendritic cells (BMDCs) were assessed. The role of CD11b DCs was analyzed using flow cytometry, cytokine assays, and adoptive transfer experiments. Epithelial-derived alarmins and type 2 innate lymphoid cells (ILC2s) were also examined. Acupuncture significantly reduced AHR, immune cell infiltration, goblet cell hyperplasia, and serum IgE levels in HDM-induced allergic asthma. It also suppressed Th2 cytokine production and differentiation. While acupuncture serum did not directly affect T cell activation, it modulated BMDC activity. Adoptive transfer of acupuncture-treated lung DCs into asthmatic mice reduced Th2 cell recruitment and ameliorated airway inflammation. Acupuncture reduced the population of lung CD11b DCs and downregulated the expression of activation markers such as CD86 and OX40L, along with Th2-promoting chemokines CCL17 and CCL22. Furthermore, it influenced CD11b DC migration by modulating CCR7, CCL2, and CCL8 expression. Acupuncture suppressed epithelial-derived alarmins IL-25, IL-33, and TSLP, attenuating ILC2 accumulation and activation, which indirectly affected CD11b DCs and Th2 responses. Acupuncture alleviates Th2 airway inflammation in allergic asthma by modulating lung CD11b DC activities. These findings provide new insights into acupuncture-based therapeutic strategies for asthma.